PENGARUH KECERDASAN INTRAPERSONAL TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Wahyu Nur Annisa; Maya Nurfitriyanti; Aulia Masruroh (IKIP Siliwangi, 2023)
The research, which was conducted at SMK Al-Barokah, aims to determine the effect of interpersonal intelegence to understanding of students' mathematical concepts. This study uses a quantitative approach with the sampling technique used is total sampling. The sampel of this study were 14 students of class XI consisting of 6 boys and 8 girls. The research instrument used was a questionnaire and an integral material description test. The technique data analys are descriptive statistical test, data analysis prerequisite test, and hypothesis analysis. The results of data analysis that there was significant influence between intrapersonal intelligence on students' understanding of mathematical concepts. This shows that the research hypothesis is accepted, meaning that intrapersonal intelligence contributes to students' understanding of mathematical concepts. As for other factors that influence students' understanding of mathematical concepts, namely student psychology, student character, attitudes towards learning, learning motivation, learning concentration, processing learning materials, exploring learning outcomes, self-confidence, and study habits.